The Effect of Financial and Non-Financial Compensation on Employee Performance Kentucky Fried Chicken (KFC) Pettarani Makassar - Muhtazib, Muhtazib; Niartiningsih, Andi (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
The purpose of this study is to determine the effect of financial compensation on the performance of KFC Pettarani Makassar employees, the effect of non-financial compensation on the performance of KFC Pettarani Makassar employees, and the effect of financial and non-financial compensation on the performance of KFC Pettarani Makassar employees concurrently. The sample for this research consisted of 42 respondents who were randomly assigned to work at KFC Pettarani Makassar. The classical assumption test, multiple linear regression analysis, T test, correlation analysis, and determination are all employed in this work. The results indicate that the hypothesis of financial compensation having an effect on employee performance is accepted based on the calculated T value of 3.357, which is greater than the T table value of 1.68488; the hypothesis of non-financial compensation having an effect on employee performance is accepted based on the calculated T value of 2.619, which is greater than the T table value of 1.68488; and financial compensation and non-financial compensation both have an effect on employee performance based on the calculated T values of The correlation coefficient test indicates that financial compensation and non-financial compensation have a strong relationship with employee performance, and the determination test indicates that financial compensation and non-financial compensation account for 51.1 percent of employee performance. It is advised that more attention be paid to the supply of incentive pay, so that by providing such compensation, the organization may increase its workers' performance; also, it is determined if the distribution is regular and the quantity offered is appropriate.